2005
DOI: 10.1097/01.sla.0000157131.84130.12
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Tissue and Wound Complications in Gastrointestinal Surgery

Abstract: Factors known to affect the process of tissue and wound healing are independently associated with tissue and wound complications following gastrointestinal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
140
4
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 226 publications
(166 citation statements)
references
References 36 publications
7
140
4
9
Order By: Relevance
“…Data from previous study demonstrated that baccy had been shown to impair tissue healing and increase the risk of wound complications and AL after gastrointestinal surgery (Kasperk et al, 2000;Sorensen et al, 2005). However, the current study provide evidence that smoking is not a independent factor of AL after the multivariate analysis.…”
Section: Discussioncontrasting
confidence: 51%
“…Data from previous study demonstrated that baccy had been shown to impair tissue healing and increase the risk of wound complications and AL after gastrointestinal surgery (Kasperk et al, 2000;Sorensen et al, 2005). However, the current study provide evidence that smoking is not a independent factor of AL after the multivariate analysis.…”
Section: Discussioncontrasting
confidence: 51%
“…Reoperation is well known as a major predictor of tissue and wound complications, or SSI, in gastrointestinal surgery. 22 ' 23 This is presumably due to the effect of longer exposure to the risk of bacterial contamination and impaired healing of the relatively avascular scar tissue of the previous incisional wound. 24 Concurrent multiple surgical procedures were also a major risk factor for SSI after gastric surgery in another study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the length of smoking cessation necessary to reduce AL is still debatable. Sørensen et al conducted a randomized controlled trial (RCT) and reported that two weeks of smoking cessation was not enough to reduce complications after colorectal resection 24) . On the other hand, a recent meta-analysis showed that at least three to four weeks of smoking cessation reduced wound-healing complications 25) .…”
Section: Discussionmentioning
confidence: 99%